Delineating the CCDC22‐related Ritscher–Schinzel syndrome phenotype in the original family. Issue 11 (8th September 2022) - Rodgers, Jonathan; Richmond, Christopher M.; McGaughran, Julie
Abstract: Pathogenic variants in CCDC22 were initially described in 2012 in a large Australian family with intellectual disability and were subsequently noted to cause a phenotype consistent with the previously described Ritscher–Schinzel syndrome (RSS). The phenotypes of the original family were not described in detail and remains limited phenotypic data reported in medical literature. We detail the phenotypes of the original family, including newly diagnosed family members. With these eight phenotypic descriptions, more than triple the number of individuals for whom detailed clinical information is available. In addition to typical facies, common phenotypic features included intellectual disability, congenital heart disease and posterior fossa malformations, postnatal short stature, ectodermal abnormalities, and digital anomalies as previously described. Spinal curvature and genital anomalies were seen in most patients, while gastrointestinal features and disturbed sleep were also recurrently seen. We propose a possible mechanism linking the familial variant to a diagnosis of sarcoidosis in one individual. Given the clinical and genetic heterogeneity of RSS, we suggest a dyadic naming convention.